The Effects of Biodiesel on NOx Emissions for Automotive Transport - Kolodnytska, Ruslana; Kravchenko, Oleksandr; Gerlici, Juraj; Kravchenko, Kateryna (Communications - Scientific Letters of the University of Zilina, 2022)
Automobiles with internal combustion engine using diesel fuel have large harmful emissions of nitrogen oxides and soot, which affect the health of the population and especially children and carbon dioxide, which is dangerous for the planet as a whole. Biodiesel is used in Europe as an additive to diesel fuel to reduce soot emissions (including carcinogens), as well as to improve the balance of carbon dioxide on the planet. Using the biodiesel in internal combustion engines tends to show higher nitrogen oxides emissions compared to diesel. In this paper, the impact of flame temperature, ignition delay and density on NOx formation of biodiesel and its component for both stationary engine and automotive engine were analysed. Emissions of nitrogen oxides increase with increasing load. In no-load modes, biodiesel shows lower emissions of nitrogen oxides than diesel.
Keywords: automotive transport; nitrogen oxides; biodiesel; ignition delay; flame temperature